1957
DOI: 10.1071/ar9570325
|View full text |Cite
|
Sign up to set email alerts
|

Bunch spear grass dominance in burnt pastures in South-Eastern Queensland

Abstract: The results are reported of a study of the effect of annual burning, in the absence of grazing, on the botanical composition of a native pasture in south-eastern Queensland. The main effect of burning was to give dominance of Heteropogon contortus (L.) Beauv. ex R. & S. This appeared to be due to three main causes: established plants were resistant to fire; fire favoured the germination of seed; and fire reduced the basal ground cover of other species. The effects on other species and on the proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1959
1959
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Thus it may be said that spear grass fires, which are a normal feature of management of the spear grass region, do not enhance germination, nor are the temperatures experienced in the surface soil under spear grass fires sufficiently great to reduce seed viability (Tothill & Shaw 1968). The lack of any response by H. contortus seed per se to grass fires confirms the opinion of Shaw (1957) that the effect of fire in promoting the dominance of spear grass is not due to direct stimulation of seed germination, but rather to an indirect effect of the interaction of grazing and herbage removal by burning. Tothill (1969) has suggested that the removal of herbage by burning has a marked effect on the diurnal temperature maximum and this promotes both early herbage regrowth and seed germination in spring.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus it may be said that spear grass fires, which are a normal feature of management of the spear grass region, do not enhance germination, nor are the temperatures experienced in the surface soil under spear grass fires sufficiently great to reduce seed viability (Tothill & Shaw 1968). The lack of any response by H. contortus seed per se to grass fires confirms the opinion of Shaw (1957) that the effect of fire in promoting the dominance of spear grass is not due to direct stimulation of seed germination, but rather to an indirect effect of the interaction of grazing and herbage removal by burning. Tothill (1969) has suggested that the removal of herbage by burning has a marked effect on the diurnal temperature maximum and this promotes both early herbage regrowth and seed germination in spring.…”
Section: Discussionsupporting
confidence: 78%
“…Initially interest in the germination of H. contortus stemmed from the way that spear grass became dominant in the native pastures in south-east Queensland as a result of grazing coupled with regular spring burning (Shaw 1957) and the carpet of spear grass seedlings to be seen developing after burning. Subsequently the need to raise plants from seed led to a reahzation that there were problems associated with germinating seeds which were anything but the simple situation apparent in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Annual burning during the dry season favours dominance of H eteropogon (Shaw 1957) and light grazing may enhance this at least where Themeda is an associate (Isbell 1969). Features of the tolerance of Heteropogon to fire are: (i) resistance of established plants to fire (Shaw 1957); (ii) promotion of seed germination by fire (Shaw 1957); (iii) seed burial by hygroscopic-awn behaviour (Tothill 1969); (iv) common failure of associate species under annual burning (Shaw 1957, Tothill 1969); (v) seed production in the wet season following fire.…”
Section: (C) Daviesia Mimosoidesmentioning
confidence: 98%
“…Thirty-three degrees of latitude are covered with a wide range of environments and vegetation types (see Leeper 1970), and with different peak periods of fire occurrence ( In the extensive coastal and subcoastal savannahs and savannah woodlands of north and north-eastern Australia where monsoonal conditions prevail, winter and spring fires are often of annual or biennial occurrence (Shaw 1957, Norman 1963, Stocker 1966. In the forested areas of the south-west and south-east, however, fires are less frequent but tend to be more devastating, especially in dry summers, as has been shown by periodical holocausts in Victoria (Vines 1970) and Tasmania (Jackson 1968b).…”
Section: (B) Geographicalmentioning
confidence: 99%
“…The season of fire can have important implications on plant responses depending on whether it occurs prior to seed set, or whether fire coincides with periods of plant growth, because wet season burning can reduce the abundance of some perennial and annual species (Stocker & Sturtz 1966; Williams & Lane 1999). Late dry season fires can promote the abundance of some grasses, such as Heteropogon contortus , whereas earlier dry season fires may promote others, including Themeda triandra (Shaw 1957; Walker et al . 1989; Orr et al .…”
Section: Introductionmentioning
confidence: 99%